2021
DOI: 10.48550/arxiv.2108.01852
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Semi-supervised Conditional GAN for Simultaneous Generation and Detection of Phishing URLs: A Game theoretic Perspective

Abstract: Spear Phishing is a type of cyber-attack where the attacker sends hyperlinks through email on well-researched targets. The objective is to obtain sensitive information such as name, credentials, credit card numbers, or other crucial data by imitating oneself as a trustworthy website. According to a recent report, phishing incidents nearly doubled in frequency in 2020. In recent times, machine learning techniques have become the standard for defending against such attacks. Many augmentations have been made for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Once utilities converge to steady points, they indicate equilibrium strategies. Moreover, we utilize GAN and GDM to generate another two sets of new images, simulating two new games 13 . Following these implementation details, the performance of equilibrium strategies can be evaluated under new generated game scenarios, with the strategy (150, 75, 75) serving as the baseline for the average scheme.…”
Section: Case Study and Results Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Once utilities converge to steady points, they indicate equilibrium strategies. Moreover, we utilize GAN and GDM to generate another two sets of new images, simulating two new games 13 . Following these implementation details, the performance of equilibrium strategies can be evaluated under new generated game scenarios, with the strategy (150, 75, 75) serving as the baseline for the average scheme.…”
Section: Case Study and Results Analysismentioning
confidence: 99%
“…For instance, deep learning-based Spear Phishing attack defense schemes often neglect attacker models, potentially undermining defense efficacy. To address such a concern,[13] utilizes GAN to design games between the attacker and defender in training and deployment phases. Numerical results have shown that the proposed scheme can realize 0.9552 Area Under Curve (AUC) on Phishing uniform resource locator (URL) classification performance, while baselines Support Vector Machine (SVM), CNN, and LSTM are with 0.8638, 0.9251, and 0.9471 AUC values, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, customers who thought they had bought bitcoin (BTC) and tried to access their funds found that their money had simply disappeared [7]. Spear phishing on CCE is a type of cyber attack in which attackers send hyperlinks, for example, using email, to well-researched targets [8], [9]. The purpose of such attacks is to obtain sensitive information by imitating trusted websites.…”
Section: Introductionmentioning
confidence: 99%